PENGARUH PERMAINAN JEMURAN KATA TERHADAP KEMAMPUAN MENGENAL HURUF PADA ANAK USIA 4-5 TAHUN DI TK ISLAM TERPADU INSAN UTAMA 2 KECAMATAN TAMPAN KOTA PEKANBARU - Bunga Anjelina; Wusono Indarto; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The research aims to determine the effect on the ability of word games clothesline recognize letters in children aged 4-5 years in TK Islam Integrated Insan Utama 2 Subdistrict of Tampan Pekanbaru city. The subjects in this study is children aged 4-5 years who totaled 14 people. The method used pre-experimental design with one group pretest posttest design that experiments conducted on one group alone with no comparison group. The technique of collecting the data in this research is observasion with observasion sheet. Based on the results obtained by testing the hypothesis that there is an influence on the ability of word games clothesline recognize letters in children aged 4-5 years in TK Islam Integrated Insan Utama 2 Subdistrict of Tampan Pekanbaru city. Retrieved t-count of 14.057 with the table = 1,770 then we can conclude that there are differences in the ability to know the letters were significant before and after using the word clothesline game. So it means that can be concluded influence clothesline word game on the ability to know the letters in children aged 4-5 years in TK Islam Integrated Insan Utama 2 Subdistrict of Tampan Pekanbaru City, with great influence 54.62%.Keywords : Recognize Letters, Clothesline Word